Understanding context in the implementation of emergency obstetric and neonatal care in health facilities in Osun State, Nigeria- a mixed-methods study - Abiola Olubusola Komolafe; Oyeyemi Olajumoke Oyelade; Sunday Adepoju Adedini; Omolola Oladunni Irinoye (BMC, 2022)
Abstract Background Successful implementation of Emergency Obstetric and Neonatal Care (EmONC) is likely to improve pregnancy outcomes and is essential for quality maternity care. Context in implementation is described as factors that enabled or disabled implementation of interventions. While the context of implementation is important for the effectiveness of evidence-based interventions, the context of EmONC implementation has not been widely studied in Nigeria. Methods The research design was cross-sectional descriptive. A mixed-methods approach was used to assess and explore the context of implementing EmONC in referral centres in Osun state. A purposive sampling technique was used to select the three tertiary health facilities in Osun State and six secondary health facilities from the six administrative zones in the State. A total of 186 healthcare providers in these referral centres participated in the quantitative part of the study, and eighteen in-depth interviews were conducted for its qualitative aspect. An adapted questionnaire from Context Assessment Index and an interview guide were used to collect data. Quantitative data were analysed using descriptive and inferential statistics at 0.05 significance level, while qualitative data were analysed using the thematic approach. Results The percentage mean score of context strength in EmONC implementation was 63% ± 10.46 in secondary and 68% ± 10.47 in tertiary health facilities. There was a significant difference in the leadership (F (1, 184) = 8.35, p < 0.01), evaluation (F (1, 184) = 5.35, p = 0.02) and overall context (F (1, 184) = 6.46, p = 0.01) of EmONC implementation in secondary and tertiary health facilities. Emerging themes in EmONC context were: Resources for EmONC implementation; Demand for EmONC; Efficiency of funding; Institutional leadership; and Performance evaluation. Conclusions The context of EmONC implementation in the referral health facilities was generally weak. The secondary health facilities' weaknesses were worse compared to the tertiary health facilities. The five key contextual factors could inform strategies for improving EmONC implementation in health facilities to ensure improved access to care that will reduce deaths from obstetric complications in Nigeria.